Luc’s Abscess: a reminder of a potential complication of otitis media - Asha'ari, Zamzil Amin; Shiyuti, Muhd Izani; Zihni, Muhammad (Ministry of Health and Universiti Brunei Darussalem, 2012)
Otitis media is still a common infection and can be associated with complications if not treated early. We report the case of an elderly gentleman who presented with an abscess deep to the temporalis muscle ‘Luc’s abscess’, as a complication of otitis media. Henry Luc first described this condition a century ago and in the antibiotic era, such manifestation is now rarely seen. We report the case of a 73- year-old man diagnosed with Luc’s abscess who presented with a week’s history of right temporal swelling that was associated with fever, right ear pain and progressive hearing impairment. This case report is a reminder to clinicians of this rare but treatable complication of a very common disease in the community.